Kinetic Pathway Control in the Synthesis of Well‐Defined Ruthenium Coordination Oligomers - Tilman Schneider; Florian Seebauer; Frank Würthner; Florian Beuerle (Small Science)
Ruthenium complexes with 2,2′‐bipyridine‐6,6′‐dicarboxylate (bda) ligands have emerged as highly potent catalysts for water oxidation. In this context, the accumulation of active Ru centers in macrocyclic arrays or coordination oligomers and polymers has proven to be very beneficial for an enhanced stability under operating conditions and to facilitate surface adhesion in heterogeneous systems. For a better insight into structure–activity relationships though, well–defined systems with a precise control over stoichiometry and constitution are highly desired. Herein, the synthesis and characterization of a series of structurally precise and monodisperse linear coordination oligomers [(Ru(bda))nLn−1pic2] (n = 4 or 5, L = 4,4′‐bipyridine or 1,4‐bis‐(pyridine‐4‐yl)benzene derivatives, pic = 4‐picoline), in excellent purity and yields are reported. Based on detailed mechanistic investigations, a complex network of interconnected and competing reactions is proposed that fully explains both the high overall turnover and the kinetic pathway selection between alternative endcapping and dissociation–elongation sequences.